O significado da espiritualidade/religiosidade no enfrentamento de paciente em cuidados paliativos. - Pinho., Juliana Ataide Melo de. (2019)
The present study aimed to investigate the state of the art about the mean ingof spirituality /religiosity in coping with palliatite care patients and their families, as evidenced in the national and international literature. Using as searchsourcesthe Virtual Health Library (VHL) ofthe Medical Literature Analysis and Retrieval System Online (MEDLINE / Pubmed), the Latin American and Caribbean Health Sciences Literature (LILACS) and the electron iclibrary Scientific Electronic Library Online (SciELO). 15publicationswereselected, whose textual analyze sallowed the construction of two categories o fanalysis: Spiritual assistance in the context of palliative care; and, Spirituality / religiosity as a way of coping in palliative care. The importance of spiritual assistanceduringtheofferofpalliativecarewasverifiedbecausespiritualityacts as a form of coping for patients and family members from the diagnosis of the disease until its final phase.